Implementation of Artificial Intelligence Technology in Financial Accounting Processes - Sri Rahmawati; Hikmah Hikmah; Rani Suharni; William Anderson (Gema Cendekia Institute, 2026)
The development of Artificial Intelligence (AI) technology has brought significant changes across various fields, including financial accounting. The implementation of AI enables accounting processes to be carried out more efficiently, accurately, and in real time through the automation of transaction recording, financial data analysis, as well as error and fraud detection. This study aims to examine the application of artificial intelligence technology in financial accounting processes, the benefits generated, and the challenges faced in its implementation. The research method employed is a literature study by analyzing various scientific journals, institutional reports, and relevant publications. The findings indicate that AI is capable of improving the quality of financial reports, operational efficiency, and managerial decision making, although challenges remain regarding implementation costs, human resource readiness, as well as ethical and data security issues.